Fabrication of porous biopolymer/ metal-organic framework composite membranes for filtration applications - Alhulaybi, Zaid Abdulhamid (2020)
Due to the exponential growth of the population and industrialisation over the past decades, the demand for sustainable separations and purification technologies has rapidly increased. Membrane-based separation is one of the most promising techniques since the costs involved is significantly reduced relative to conventional technologies such as distillation which relies on energy-intensive phase changes. However, fabricating sustainable and cost-effective membranes with high separation performance and chemical/thermal stability is still a challenge. Nowadays, biopolymers derived from bio-sources have been attracting significant interest as a result of their biodegradable, recyclable and compostable nature. Poly(lactic acid) (PLA), the second most produced biopolymer, was selected for the fabrication of flat sheet porous membranes in this study. Although PLA is cheaper than other biopolymers, it is relatively soft and has a low modulus and thus additives can be used to stiffen the structure. In this work, the influence of incorporating metal-organic framework (MOF) particles into a PLA matrix was explored through the fabrication of PLA/MOF mixed matrix membranes (MMMs) with the aim of improving mechanical and separation performance i.e. selectivity. The essential novelty of this research is in the fabrication of biodegradable and sustainable flat sheet porous PLA films by the phase inversion method-immersion precipitation technique. In addition, PLA/MOFs mixed matrix porous films are being made for the first time in order to incorporate various types of MOFs into the PLA phase by using the same fabrication technique that produces porous membranes. The effect of fabrication conditions such as the initial crystallinity and concentration of PLA, the type of a non-solvent bath, drying conditions and casting thickness was first explored for pure PLA membranes. Scanning electron microscope (SEM) images showed that membranes had an asymmetric skinned layer which is supported by a thicker porous structure. After some experiments, the polymer concentration was settled at 10 wt% PLA in dimethyl sulfoxide (DMSO) solvent. Pure PLA membranes with a 50 µm casting thickness exhibited a homogeneous structure without shrinkage or excessive brittleness. After establishing viable fabrication conditions for pure PLA membranes, PLA/MOF MMMs were then fabricated using established MOFs HKUST-1 and MIL-53. The presence of HKUST-1 and MIL-53 crystals in the PLA matrix was confirmed using X-ray diffractometry (XRD). During the preparation of 5 wt% HKUST-1 loaded PLA/HKUST-1 MMMs, the influence of casting thickness, immersion time and temperature were investigated. Results demonstrated that for PLA/HKUST-1 MMMs cast with a thickness of 50 µm and immersed for 90 minutes at 25 oC was adequate to obtain a homogeneous structure. The influence of increasing HKUST-1 loading, up to 40 wt%, into PLA matrix was also considered. The PLA/HKUST-1 MMMs were successfully fabricated for 5, 10 and 20 wt% HKUST-1 loading. Membrane porosity was increased slightly as HKUST-1 loading increased. However, PLA/HKUST-1 MMMs became increasingly brittle beyond 5 wt% loading which was observed via a tensile strength test. Mechanical and degradation tests were performed to examine the membrane durability. Pure PLA and PLA/HKUST-1 membranes exhibited a tensile strength of ~1-1.5 MPa and ~0.5-1 MPa, respectively. This suggests that the inclusion of HKUST-1 did not improve the stiffness. Degradation studies showed that pure PLA membranes were capable of withstanding temperature conditions of 50 oC in a water environment for approximately two months, estimated as equivalent to ~2 years at 25 oC, before any significant loss in mechanical strength could be observed. Pure water successfully passed through all PLA membranes, with flux recorded as high as 1000 l m-2 h-1 at 6 bar feed pressure for a porous membrane of 700 microns in thickness. Membrane microstructure, overall thickness, porosity and the applied pressure influenced water flux. Membrane separation performance was also examined using a number of micron-size particles including corn flour, cement, milk powder, dye and ground coffee. For corn flour particles, pure PLA and 5-20 wt% HKUST-1 loaded PLA/HKUST-1 membranes with ~288-348 µm thickness, exhibited particle rejections of more than 90%.